2013
DOI: 10.1016/j.ygcen.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Faecal cortisol metabolites in Bengal (Panthera tigris tigris) and Sumatran tigers (Panthera tigris sumatrae)

Abstract: The tiger (Panthera tigris) faces a great risk of extinction as its wild numbers have plummeted due to poaching and habitat destruction so ex-situ conservation programs are becoming ever more necessary. Reliable non-invasive biomarkers of the stress hormone (cortisol) are necessary for assessing the health and welfare of tigers in captivity. To our knowledge, non-invasive stress endocrinology methods have not been tested as widely in tigers. The first aim of this study was to describe and validate a faecal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 46 publications
7
36
0
1
Order By: Relevance
“…This study demonstrated that tiger stress levels were significantly different between sexes and zoos, matching with previous studies that also found higher average stress levels in females than males for other felids [18]. Narayan et al's [8] study also showed that individual tigers responded differently to the stressor type, intensity and duration. This highlights the phenomenon of unique personalities or coping abilities in animals [19].…”
Section: Tiger Stress Biology Research In Captivity 31 Conservationsupporting
confidence: 88%
See 3 more Smart Citations
“…This study demonstrated that tiger stress levels were significantly different between sexes and zoos, matching with previous studies that also found higher average stress levels in females than males for other felids [18]. Narayan et al's [8] study also showed that individual tigers responded differently to the stressor type, intensity and duration. This highlights the phenomenon of unique personalities or coping abilities in animals [19].…”
Section: Tiger Stress Biology Research In Captivity 31 Conservationsupporting
confidence: 88%
“…Glucocorticoids or stress hormones (e.g. corticosterone and cortisol in tigers) are released into systemic blood circulation during the initiation of the physiological stress response [8]. This occurs when a stimulus (e.g.…”
Section: Stress Physiology Of Tigersmentioning
confidence: 99%
See 2 more Smart Citations
“…In our 8 study, as well as these other investigations, inter-individual and intersexual variation in fGCM levels appears high. However, it is highly likely that the marked intersexual difference suggested by the post-ACTH data was linked to the injury that the female had sustained during the capture procedure (see also Muenscher et al 2010;Narayan et al 2013). We found no clear, unidirectional intersexual differences in circulating cortisol levels or fGCM, and therefore predict that larger studies will find healthy male foxes exhibiting cortisol levels comparable to non-lactating female bat-eared foxes.…”
Section: Discussionmentioning
confidence: 47%